2020
DOI: 10.15366/reim2020.28.005
|View full text |Cite
|
Sign up to set email alerts
|

The Civil Society, the Commune, the Parliament: strategies for political promotion of young rural leaders in the province of El Hajeb, Morocco

Abstract: Bearing in mind that elections are an auspicious time to raise local political issues, this article analyses the strategies of young men and women leaders inthe province of El Hajeb in Morocco and how they negotiate their leadership roles at the local level. The article is based on observations and semi-structured interviews conducted with young leaders and resource holdersduring the legislative elections of October 2016. While some young people manage to accessmunicipal councils, the present authorsfind evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The interviewees we met during this study put forward their willingness to address the needs of members or inhabitants. However, the diversification of activities may also have been driven by other motives, such as the willingness to seize funding opportunities, the leaders' own employment or career objectives (Ftouhi et al, 2020)—and several motives may be present at the same time. Several authors reported cases of LDOs in rural areas of North Africa in which a small elite, who were the only people with the skills and social networks needed to interact with donors, failed to share decision making with other members.…”
Section: Discussionmentioning
confidence: 99%
“…The interviewees we met during this study put forward their willingness to address the needs of members or inhabitants. However, the diversification of activities may also have been driven by other motives, such as the willingness to seize funding opportunities, the leaders' own employment or career objectives (Ftouhi et al, 2020)—and several motives may be present at the same time. Several authors reported cases of LDOs in rural areas of North Africa in which a small elite, who were the only people with the skills and social networks needed to interact with donors, failed to share decision making with other members.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the rural youth and their emerging associations have often been excluded from participative governance settings, such as local development committees within the framework of the INDH, as well as from the financial support programmes (Giuliani et al 2017). young people often experience difficulties in accessing authorities, as they usually lack the social networks and material resources to do so (Ftouhi, Kadiri, and Mahdi 2020). Hence, the disaffection among a younger generation in rural areas has supported the adoption of positions and ideas that diverge from those of their elders.…”
Section: Imaginary Construction Sites For An Inclusive Green Modernitymentioning
confidence: 99%